CONTEXTUAL MODEL APPLICATION TO IMPROVE STUDENT LEARNING OUTCOMES IN LEARNING CONCEPT TWO-DIMENTIONAL FIGURE - Sunimah, Nani (Prodi Teknologi Pendidikan, 2016)
Abstract. Cilengkrang Elementary School second grade students in learning are still having trouble getting up flat. Based on early research on learning outcomes, students who completed study on indicators to use a formula to calculate the flat wake, only reached 25%. To overcome this implemented so that students understand the contextual model for teaching students associated with the real world. The method used in this research is a classroom action research methods to the design of the research procedure refers to the spiral model Kemmis and MC. Taggart. Research data collection techniques are observation, interviews, field notes, and tests using instruments guidelines for observation, interview, field notes, journals and tests. As for data validation, used techniques chek members, triangulation, audit trail and expert opinion. Based on the implementation of the actions carried out by two cycles, as a whole has shown an increase from the initial data, both process and outcomes of learning. From the data obtained, the process of learning to teacher performance, tahapperencanaan the first cycle to IImencapai 100%, during the implementation phase, the first cycle of 75% and the second cycle of 100%, at this stage of the evaluation cycle I to II reached 100% target achievement completeness 80 %. On the percentage of student activity average values, the first cycle and the second cycle 67% 82% with a target of achieving completeness ≥ 80.64%. As for the study results, the percentage ketuntasannya, the first cycle and the second cycle 42% 87% with a target of achieving completeness ≥ 80.64%. So that the application of contextual models can enhance students' understanding of the class II SDN Cilengkrang Northern District of Sumedang Sumedang Regency to the concept of a flat wake. Keywords: Build Flat, Contextual Model, Mathematics Education Abstrak. Siswa kelas II SDN Cilengkrang dalam pembelajaran bangun datar masih mengalami kesulitan. Berdasarkan penelitian awal pada hasil belajar, siswa yang tuntas belajar pada indikator menggunakan rumus untuk menghitung bangun datar, hanya mencapai 25%. Untuk mengatasi hal tersebut diterapkan model kontekstual agar siswa paham karena pembelajaran dikaitkan dengan dunia nyata siswa. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas dengan rancangan prosedur penelitiannya mengacu pada model spiral Kemmis dan MC. Taggart. Teknik pengumpulan data penelitian yang digunakan adalah observasi, wawancara, catatan lapangan, dan tes dengan menggunakan instrumen pedoman observasi, pedoman wawancara, catatan lapangan, jurnal dan tes. Sedangkan untuk validasi data, digunakan teknik member chek, triangulasi,audit trail dan expert opinion. Berdasarkan pelaksanaan tindakan yang dilakukan sebanyak dua siklus, secara keseluruhan telah menunjukan adanya peningkatan dari data awal, baik dalam proses maupun hasil belajar. Dari data yang diperoleh, pada proses pembelajaran, untuk kinerja guru, tahapperencanaan siklus I sampai IImencapai 100%, pada tahap pelaksanaan, siklus I 75% dan siklus II 100 %, pada tahap evaluasi siklus I sampai II mencapai 100 % dengan target pencapaian ketuntasan 80 %. Pada aktivitas siswa persentase nilai rata-rata, siklus I 67%dan siklus II 82% dengan target pencapaian ketuntasan ≥ 80,64 %. Sedangkan untuk hasil belajar, persentase ketuntasannya, siklus I 42 %dan siklus II 87% dengan target pencapaian ketuntasan ≥ 80,64 %. Sehingga penerapan model kontekstual dapat meningkatkan pemahaman siswa kelas II SDN Cilengkrang Kecamatan Sumedang Utara Kabupaten Sumedang terhadap konsep bangun datar. Kata Kunci: Bangun Datar, Model Kontekstual, Pendidikan Matematika